Legal and ethical aspects of development of molecular genetic technologies - Irina TuzankinaLyudmila Voronina, Екaterinа Zaitseva, Andrey Nechkin, (Opción, 2019)
This research aims to understand the concept of molecular genetic technologies and other types of studies relating to innate immunity errors by using the comparative method. The authors borrowed the results of the sociological researches conducted by Russian scientists in the framework of the international research program Genetics and Ethics as well as the expertise of their own specialists of genetic laboratories in Yekaterinburg (Russia, n = 16). In conclusion, it is also advisable to prohibit an unborn child genetic test for the identification of the diseases that may appear in adulthood.